Merrian websters collegiate dictionary - Merriam-Webster's, Incorporated (Massachusttes: Merriam-webters, 2001)
Contents : guide to pronunciation, abbreviation in this work, pronunciation symbols, abbreviations and symbols for chemical elements, foreign words and ohrases, biographical names, geographical names, signs and symbols a hand book of style, index
Incluye index
Keywords: Diccionario - Inglés